Mycophenolate Mofetil Use Is Associated With Reduced Incidence of Food Allergy in Liver Transplanted Children. Issue 2 (6th June 2022) - Haflidadottir, Svanhildur; Østensen, Anniken Bjørnstad; Matthews, Iren Lindbak; Line, Pål-Dag; Almaas, Runar
Abstract : Objectives: The incidence of food allergy in children following liver transplantation is high, and the pathogenesis is still not known. We aimed to identify risk factors for development of food allergies in liver transplant children. Methods: One hundred seven children and adolescents who underwent liver transplantation from 1999 to 2019 were included. Data were retrospectively collected from medical records and included total and specific immunoglobulin E (IgE), eosinophil cationic protein, and eosinophil count 12 months after transplantation and at yearly follow-up (median follow-up). Results: Twenty-four/107 (22%) patients reported clinical food reactions. Median time from transplantation to debut of food allergy was 1.6 [interquartile range (IQR): 0.6–3.3] years. Mycophenolate mofetil (MMF) was discontinued in 24 out of 78 patients (31%) due to side effects. Children treated with MMF in addition to tacrolimus 1 year after transplantation reported less food allergy (12.5% vs 37.8%, P = 0.003) and sensitization to food allergens one year after transplantation (8.9% vs 17.8%, P = 0.02) than those not receiving MMF. Tacrolimus trough levels did not differ between the patients treated with MMF and those who were not. Treatment with MMF 2 years after transplantation was associated with less food allergy ( P = 0.001) and food sensitization ( P = 0.002), also when adjusted for age at transplantation ( P = 0.006 and P = 0.03, respectively) or for use of basilixmab ( P = 0.015 and P = 0.018, respectively). Basiliximab was also associated with less food allergies. Conclusions: Use of MMF 1 and 2 years after transplantation was associated with less food allergy and sensitization against food allergens. The effect of MMF was not due to reduced trough levels of tacrolimus.